Refillable Containers and Secondary Containment Requirements for Agricultural Pesticides in Florida - Bonnie Wells; Frederick M. Fishel (EDIS)
This 4-page fact sheet discusses the requirements for selection and design of containers and dispensing areas, as well as operation, inspection, maintenance, and recordkeeping. Written by Bonnie Wells and F.M. Fishel, and published by the UF Department of Agronomy, January 2012.